Energy and Environmental Performance Based Decision Support Process for Early Design Stages of Residential Buildings Under Climate Change - Gerçek, Mümine; Durmuş Arsan, Zeynep; Arsan, Zeynep Durmuş (Elsevier, 2019)
Building design decisions have high impacts on energy and environmental performance of buildings. Especially, conscious decisions in earlier design stages are more significant due to lifespan impact of buildings. Deficiencies in systematic approach for design decision support to increase energy and environmental performance of buildings are projected as the major problems of this study. Decisions for performance-based design should be made in terms of the most effective design parameters peculiar for each project. This study exemplifies the act of design decision support in early design stage of a residential building in Turkey. The relation between design parameters and annual energy consumption for heating, cooling and annual operational CO2 emissions is examined by global sensitivity analyses for the present, 2020s, 2050s and 2080s weather conditions. Design process requires the assessment of the uncertainties in building performance caused both by design parameters and climate change. The results indicate that the decisions about solar heat gain coefficients (SHGC), and heat transfer coefficients (U) of transparent surfaces on building envelope have the highest impacts on energy and environmental performance of residential buildings in hot-humid climatic conditions.
Keywords: Residential buildings; Building energy and environmental performance; Sensitivity analysis; Design decision support; Climate change